Product Meaning in Digital Product Innovation - Wang, Gongtai; Henfridsson, Ola; Nandhakumar, Joe; Yoo, Youngjin (MIS Quarterly, 2022)
Digital product innovation involves a meaning-making process. Designers of digital innovations often challenge established product meanings as they digitize physical products, such as cars, toothbrushes, and water bottles. A significant problem for product designers, however, is striking the right balance between the newness and comprehensibility of product meanings. Failure to do so may result in a digital product innovation that is too conventional or difficult to relate to or understand. Yet, the extant digital product innovation literature pays little, if any, attention to product meaning. To fill this void, this study examines a digital product innovation project in which product designers created a digital theater with product meanings beyond those of the traditional movie theater. Our theory, grounded in in-depth data collection and analysis, explains how product designers attribute meanings to their products in the process of digital innovation by enacting two meaning-making loops: a reinforcing loop that makes the product meaning comprehensible, and a differentiating loop that captures emerging product meanings. The two loops come together via meaning sedimentation, through which a new core product meaning is created. Our study contributes to the digital product innovation literature by shedding light on the essential role of meaning-making in innovation and offers an explanatory process theory.